Design proposal for a continuing training course on alternative reality games for spanish teachers - Linhati, Suzana; dos Reis, Susana Cristina (The ESPecialist, 2023)
This article presents an online course prototype that uses alternative reality game mechanics as a pedagogical strategy to engage Spanish teachers in continuing education to learn about the design of digital materials. This exploratory and qualitative study, supported by the contextualized instructional design and in the MODE framework, resulted in the production of the artifact. Results of the product evaluation indicate that the prototype promotes pedagogical immersion and engagement due to its ARG design; however, technological adjustments would improve its usability and participant access in solving the challenges.